2009
DOI: 10.2340/16501977-0389
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of motor evoked potentials in motor function recovery of upper limb after stroke

Abstract: Motor evoked potentials could be a supportive tool to increase the prognostic accuracy of upper limb motor and functional outcome in hemiparetic patients, especially those with severe initial paresis (MRC < 2) and/or with motor evoked potentials absent in the post-stroke acute phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 25 publications
1
40
0
7
Order By: Relevance
“…However, the accuracy of these predictions was only marginally better than chance (55%, Table 3). The addition of TMS biomarker information increased prediction accuracy to 70% for these patients, underlining the value of testing corticospinal tract function in patients with more severe motor impairment 21, 22. While PREP2 requires TMS for a smaller proportion of patients, this does not eliminate barriers to using this technique in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the accuracy of these predictions was only marginally better than chance (55%, Table 3). The addition of TMS biomarker information increased prediction accuracy to 70% for these patients, underlining the value of testing corticospinal tract function in patients with more severe motor impairment 21, 22. While PREP2 requires TMS for a smaller proportion of patients, this does not eliminate barriers to using this technique in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Our data contribute to this issue, by suggesting that a combination of two relatively easily obtainable parameters could support decisions concerning the rehabilitation process. Some studies conducted in the acute phase of stroke showed, using MEP threshold and amplitude measures, a relationship between motor recovery and the degree of motor impairment (Pennisi et al, 1999;Pizzi et al, 2009;Rapisarda et al, 1996). The absence of MEPs, more than amplitude variations, seems to be predictive of recovery (Di Lazzaro et al, 2010), but consensus on this issue is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to evoke a motor response in the abductor digiti minimi of the affected upper limb in paralyzed patients (MRC<2) 1 week after stroke is a strong predictor of some recovery of upper limb movement 1 year after stroke. 84 The predictive ability for upper limb recovery with an MEP is quite specific (99%), meaning there are no false positives. The sensitivity on the other hand ranges from 62% to 94%, because some patients without an MEP will still regain some motor function.…”
Section: Ambulationmentioning
confidence: 99%